Carbapenemase Gene Transfer among Canadian Patients Colonized or Infected with Carbapenemase-Producing Enterobacteriaceae. (4th October 2017) - Matic, Nancy; Marchand-Austin, Alex; Borgundvaag, Emily; Mcgeer, Allison; Patel, Samir; ,
Abstract: Background: Carbapenemase-producing Enterobacteriaceae (CPE) has been declared an emerging global health threat. Plasmid transfer between species is of particular concern, allowing carbapenem resistance to spread rapidly to invasive or hypervirulent organisms which could potentially lead to severe infections. The rate of carbapenemase gene transfer between species has not been quantified to date. Methods: CPE isolates from 754 patients whom had either clinical or surveillance specimens submitted to our reference laboratory between January 2011 and December 2016 were reviewed. Patients with multiple Enterobacteriaceae species possessing the same carbapenemase gene were analyzed. Additionally, we reviewed data from a study in which rectal and groin swabs were collected from 88 patients at 3-month intervals to determine the average duration of CPE colonization prior to gene transfer. Results: Thirty-nine out of 754 patients (5.2%) showed evidence of carbapenemase gene transfer between species. The majority (34/39 patients, 87.2%) had specimens submitted at a single point in time. Most commonly, multiple species with the same carbapenemase gene were found in rectal swabs (25/286 CPE-positive rectal swabs, 8.7%) followed by urine cultures (3/327 CPE-positive urine cultures, 0.9%). In the follow-up study, 8/88 patients with at least one follow-up specimen (9.1%) showed evidence of gene transfer over time. Out of a total of 10 instances of gene transfer, 3, 2, 3, 1, and 1 were detected at the 1-, 3-, 6-, 9-, and 15-month follow-up periods, respectively. Distribution of species and gene types was similar among the index isolates and second isolates (Table 1). Conclusion: A significant minority of CPE-colonized patients will be colonized with multiple species of Enterobacteriaceae . Gene transfer to new species continues to occur over time in persistently colonized patients. Disclosures: All authors: No reported disclosures.